“We don’t worry about diabetes that much”: a qualitative study exploring perceptions of physical activity among children with Type 1 Diabetes - Quirk, Helen; Glazebrook, Cris; Martin, Rebecca; Blake, Holly (Longdom Publishing, 2016)
Background: Despite the health benefits of physical activity, children across the population are insufficiently active. Physical activity is essential in the management of Type 1 Diabetes Mellitus (T1DM), therefore its promotion should be a priority, yet little research has explored the experience of physical activity from the viewpoint of children with this condition. This study sought to provide insight into how children with T1DM perceive and participate in physical activity to further the design of initiatives and clinical interventions that promote active lifestyles in this population. Methods: Researchers collected data through in-depth interviews with twelve children aged 9-11 years with T1DM in the UK. Interviews were recorded, transcribed verbatim and data were analysed using thematic analysis. Results: The overarching themes captured: children’s understanding of physical activity; children’s physical activity is motivated by friendship and social interaction; children’s physical activity is motivated by positive perceptions, fun and enjoyment; children describe how their family helps them to be active; school provides children with an opportunity to be active; children’s access to facilities and outdoor space encourages physical activity; children refer to personal mastery and competence in physical activity and; children perceive difficulties that make physical activity harder. Conclusions: This study is the first to distinguish children’s perceptions toward physical activity from other key stakeholders. Listening to children has identified what they believe is important, for example enjoyment and socialisation, which should be considered when developing strategies to promote physical activity in this population.